The narcissistic robot: Robot calibration using a mirror - Ruther, M; Lenz, M; Bischof, H (2010 11th International Conference on Control Automation Robotics and Vision, 2010)
We present a novel method for calibration of a robotic manipulator. The robot kinematic chain and its tool are observed by a hand mounted camera through a mirror. We show the possibility of enabling hand-eye, hand-tool, and kinematic robot calibration without incorporating accurate external references, except the mirror. Using this particularly simple setup, hand-eye calibration becomes independent of the kinematic chain and parameter observability constraints in kinematic calibration become more relaxed, which makes pose planning for robot calibration more convenient.